2011
DOI: 10.1073/pnas.1018132108
|View full text |Cite
|
Sign up to set email alerts
|

Wnt7a signaling promotes dendritic spine growth and synaptic strength through Ca 2+ /Calmodulin-dependent protein kinase II

Abstract: The balance between excitatory and inhibitory synapses is crucial for normal brain function. Wnt proteins stimulate synapse formation by increasing synaptic assembly. However, it is unclear whether Wnt signaling differentially regulates the formation of excitatory and inhibitory synapses. Here, we demonstrate that Wnt7a preferentially stimulates excitatory synapse formation and function. In hippocampal neurons, Wnt7a increases the number of excitatory synapses, whereas inhibitory synapses are unaffected. Wnt7a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
250
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(262 citation statements)
references
References 48 publications
11
250
0
1
Order By: Relevance
“…Wnt-5a KO results in defects in dopaminergic neurogenesis and neurite development [44,45], and Wnt-7a KO impairs maturation of dopaminergic and other neuronal populations [46][47][48] (Table 1). While Wnt-3a has been described as canonical, Wnt-5a is generally associated with noncanonical Wnt signaling [49], and Wnt-7a is frequently found to play both canonical and noncanonical roles [50 , 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 51].…”
Section: Wnt Signaling In the Mouse Brain: Wnt Ligands And Receptorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wnt-5a KO results in defects in dopaminergic neurogenesis and neurite development [44,45], and Wnt-7a KO impairs maturation of dopaminergic and other neuronal populations [46][47][48] (Table 1). While Wnt-3a has been described as canonical, Wnt-5a is generally associated with noncanonical Wnt signaling [49], and Wnt-7a is frequently found to play both canonical and noncanonical roles [50 , 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 51].…”
Section: Wnt Signaling In the Mouse Brain: Wnt Ligands And Receptorsmentioning
confidence: 99%
“…Induced proliferation of hESCs/mNSCs [65,66] Recombinant Wnt-3a Induced proliferation and differentiation of hESCs [67] Wnt-4 silencing Impaired early differentiation in hECCs [68] Wnt-5a KO Impaired neurite development in the olfactory bulb (OB) [44] Wnt-1 and Wnt-5a DKO Impaired neurogenesis of midbrain dopaminergic neurons [52] Wnt-5a KO Impaired axon growth and guidance of dopaminergic neurons [45] Wnt-5a CM Increased synaptogenesis and maturation of hippocampal progenitors [69,70] Wnt-5a overexpression Induced axonal differentiation in hippocampal cultures [71] Wnt-7a KO Delayed morphological maturation of glomerular rosettes and synapsin I accumulation [46] Wnt-7a KO Impaired ventral midbrain neurogenesis [47] Wnt-7a and Dvl DKO Defective spine morphogenesis and mossy fiber-CA3 synaptic transmission [48] Wnt-7a Proposed as a key element in the regulation of NSC self-renewal/differentiation; altered spindle- Canonical Wnt receptors are also important for correct neural development (Table 2): FZD3 KO mice show impaired axonal guidance [73] while LRP6 KO mice present cortical defects [74]. Also, FZD1 has been shown to be the receptor for canonical Wnt-1 in mouse tyrosine hydroxylase positive neurons, which activates β-catenin-dependent signaling promoting neuroprotection in dopaminergic neurons [75].…”
Section: Neural Phenotype In Mammalian Models Referencementioning
confidence: 99%
See 1 more Smart Citation
“…In axons, Wnts activate a canonical Wnt signaling pathway that requires inhibition of Gsk3 (Ahmad-Annuar et al, 2006;Cerpa et al, 2008b;Davis et al, 2008). On dendrites, Wnts trigger the recruitment of postsynaptic components through the activation of noncanonical pathways (FarĂ­as et al, 2009;Cuitino et al, 2010;Ciani et al, 2011). Given the role of Wnts in synaptic function, decreased levels of Wnt signaling could contribute to synaptic loss, characteristic of early states of AD.…”
Section: Introductionmentioning
confidence: 99%
“…The data has shown significant up-regulation of Wnt signaling genes in 3D such as WNT7B, WNT7A and FZD3. WNT7B and WNT7A have been shown to be involved in several developmental processes, including regulation of cell fate and patterning during embryogenesis [13][14][15]. The gene FZD3 has previously been reported that mutant mice with defects in frizzled family receptors such as FZD3 showed a severe impairment of midbrain morphogenesis [13,16].…”
Section: Discussionmentioning
confidence: 99%